Bioethics and Optimism at Work - Ravitsky, Vardit (The Hastings Center report, 2025)
In the coming years, we will be facing urgent and complex challenges—from climate change, aging societies, and structural inequities to the possible effects of emerging technologies like genomics and artificial intelligence. But, as the president of The Hastings Center for Bioethics, I remain optimistic because bioethics can play a crucial role in navigating this future. To be effective, the field must expand its scope, embrace systemic and global thinking, and foster inclusive conversations around divisive issues. The Hastings Center, now in its fifty-seventh year, is launching a five-year strategic plan that prioritizes promoting justice, overcoming collective-level barriers, and fostering trust and trustworthiness in science, biomedicine, and health care. Rooted in values like independence, rigor, and inclusiveness, the Center aims to translate conceptual analysis into real-world impact through actionable guidance developed collaboratively, partnerships, and public outreach. I envision a future where bioethics actively shapes just and responsible responses to such challenges, reaffirming its relevance in promoting health and flourishing across communities and nations.